2019
DOI: 10.3390/cancers11121938
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Concordance of Genomic Alterations between Circulating-Free DNA and Tumour Tissue in Cancer Patients

Abstract: Somatic alterations to the genomes of solid tumours, which in some cases represent actionable drivers, provide diagnostic and prognostic insight into these complex diseases. Spatial and longitudinal tracking of somatic genomic alterations (SGAs) in patient tumours has emerged as a new avenue of investigation, not only as a disease monitoring strategy, but also to improve our understanding of heterogeneity and clonal evolution from diagnosis through disease progression. Furthermore, analysis of circulating-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 158 publications
(145 reference statements)
3
23
0
Order By: Relevance
“…We next examined the concordance in KRAS G12/G13 mutation status as determined using ddPCR in plasma and via Sanger sequencing in FFPE samples. The overall inter-assay concordance was found to be 75.0% (N = 72/96 paired samples; k= 0.395; p < 0.001), which is similar to previous studies [ 23 , 24 ]. In 48.6% (N = 17/35 cases) of patients with KRAS mutations in tumor tissues, no mutations were detected in cfDNA.…”
Section: Discussionsupporting
confidence: 89%
“…We next examined the concordance in KRAS G12/G13 mutation status as determined using ddPCR in plasma and via Sanger sequencing in FFPE samples. The overall inter-assay concordance was found to be 75.0% (N = 72/96 paired samples; k= 0.395; p < 0.001), which is similar to previous studies [ 23 , 24 ]. In 48.6% (N = 17/35 cases) of patients with KRAS mutations in tumor tissues, no mutations were detected in cfDNA.…”
Section: Discussionsupporting
confidence: 89%
“…The TB is still the gold standard approach for most physicians at diagnosis [ 84 , 158 , 159 , 168 , 169 , 170 ]. However, a combined approach associating at the same time an NGS analysis on matched TB and LB could be of strong interest in aiming to establish a complete molecular portrait of the tumor, which can take into consideration the genomic alteration of the primary and the metastatic site(s) [ 171 , 172 , 173 , 174 , 175 ]. Though rare, if no tissue is available at diagnosis LB NGS is the only alternative in identifying a molecular alteration accessible to a targeted therapy [ 170 , 176 , 177 , 178 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrated a lower sensitivity of NGS approaches from LB samples for the detection of an ALK rearrangement, compared to matched patient tissue biopsies [ 42 ]. Moreover, some genomic anomalies including fusions, copy number alterations and some focal amplifications (in particular in MET or ALK ) seem to be more difficult to detect in blood than in tissues, as shown in a number of comparative studies [ 107 , 108 , 109 , 110 ]. It is also possible that the lower sensitivity of LB is linked to poorly controlled pre-analytical steps, (i) an inadequate amount of plasma to obtain an optimal amount of nucleic acid for analysis, and, (ii) a too long delay between sampling of blood and centrifugation, resulting in liberation of a lot of nucleic acid of germinal origin (from circulating hematological cells), which limits the analysis of plasma nucleic acids released from tumor cells [ 111 ].…”
Section: Advantages and Limitations Of Liquid Biopsy In mentioning
confidence: 99%